Hypnotic State Modulates Sensorimotor Beta Rhythms During Real Movement and Motor Imagery - Rimbert, Sébastien; Zaepffel, Manuel; Riff, Pierre; Adam, Perrine; Bougrain, Laurent (Frontiers in Psychology, 2019)
The hypnosis technique is currently used in the medical field and influences directly the patient's state of relaxation, perception of the body and its visual imagination. There is evidence to suggest that hypnosis state may help patients to better achieve the task of motor imagination, which is central in rehabilitation protocols after a stroke. However, the hypnosis technique could also alter the activity in motor cortex. To the best of our knowledge, the impact of hypnosis on the EEG signal during a movement or an imagined movement is poorly investigated. In particular, how event-related desynchronization (ERD) and event-related synchronization (ERS) patterns would be modulated for different motor tasks may provide a better understanding of the potential benefits of hypnosis for stroke rehabilitation. To investigate this purpose, we recorded EEG signals from 23 healthy volunteers who performed real movements and motor imageries in closed eye condition. Our results suggest that the state of hypnosis changes the sensorimotor beta rhythm during the ERD phase but maintains the ERS phase in the mu and beta frequency band suggesting a different activation of the motor cortex in the hypnotized state.